Beverages characterize the nutritional profile of Brazilian adolescents' breakfast. Issue 1 (December 2016) - dos Santos Correa, Alline; Rodrigues, Paulo; Monteiro, Luana; de Souza, Rita; Sichieri, Rosely; Pereira, Rosangela
Abstract Background The breakfast is the most important meal of the day, and its quality is essential for children and adolescents to maintain proper health condition. However, the nutritional composition of breakfast remains poorly studied. The aim of this study was to characterize the nutritional quality of Brazilian adolescents' breakfast. Methods This is a cross-sectional study, conducted in 2005, including 1133 students from public schools, between 10 and 14 years old, in Niterói, Brazil. Information regarding breakfast consumption was obtained using 24-h dietary recall. Cluster analysis was applied to characterize the breakfast nutritional profiles. Results Of the sample, 16 % did not have breakfast on the survey day, and skipping breakfast was more frequent among overweight than among of normal-weight individuals (20 vs. 15 %;P = 0.04) as well as among those studying in the morning shift compared to adolescents studying in the afternoon shift (18 vs. 10 %;P < 0.01). The mean daily energy, macronutrient, calcium, and vitamin A intakes were significantly higher among individuals who had breakfast compared with those who did not. The breakfast contribution to the daily energy intake was, on average, of 18 %. The food profile analysis showed that breakfast could be characterized by the type of beverage consumed in the meal, and five eating profiles were identified: "Coffee or tea, " "Milk or milk-based beverages, " "Sugar-sweetened beverages, " "No beverage consumption, " and "More than one type of beverage". Conclusions The dietary breakfast choices were related with the daily energy and nutrient intake and the type of beverage characterized the breakfast food selection among Brazilian adolescents.